Exploration of the Association between Nurses' Moral Distress and Secondary Traumatic Stress Syndrome: Implications for Patient Safety in Mental Health Services - Christodoulou-Fella, Maria; Middleton, Nicos; Papathanassoglou, Elizabeth; Karanikola, Maria (My University, 2017)
Work-related moral distress (MD) and secondary traumatic stress syndrome (STSS) may be associated with compromised health status among health professionals, reduced productivity, and inadequate safety of care. We explored the association of MD with the severity of STSS symptoms, along with the mediating role of mental distress symptoms. Associations with emotional exhaustion and professional satisfaction were also assessed. This cross-sectional survey conducted in 206 mental health nurses (MHNs) was employed across public sector community and hospital settings in Cyprus. The analysis revealed that MD (measured by the modified Moral Distress Scale) was positively associated with both STSS (measured by the Secondary Traumatic Stress Scale) and mental distress symptoms (assessed by the General Health Questionnaire-28). The association of MD with STSS symptoms was partially mediated by mental distress symptoms. This association remained largely unchanged after adjusting for gender, age, education, rank, and intention to quit the job. Our findings provide preliminary evidence on the association between MD and STSS symptomatology in MHNs. Situations that may lead health professionals to be in moral distress seem to be mainly related to the work environment; thus interventions related to organizational empowerment of MHNs need to be developed.
Keywords: Morals; Nurses; Moral sensitivity